2023
DOI: 10.3389/fonc.2023.1234045
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a prognostic signature associated with liver metastases for prognosis and immune response prediction in colorectal cancer

Abstract: BackgroundAs the most common gastrointestinal malignancy worldwide, liver metastases occur in half colorectal cancer (CRC) patients. Early detection can help treat them early and reduce mortality in patients with colorectal cancer liver metastases (CRLM). Finding useful biomarkers for CRLM is thus essential.MethodsThe TCGA and GEO databases were used to download the expression profiles and clinical data of the patients. Differential analysis screened for genes associated with CRLM, and univariate Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, the capacity of the ESTIMATE immune scores to predict immunotherapy response in cancer is controversial. 70 , 71 , 72 , 73 , 74 Gao et al. observed that the low-risk group classified by a novel pyroptosis-related signature had higher ESTIMATE immune scores and exhibited better responses to ICIs than the high-risk group in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the capacity of the ESTIMATE immune scores to predict immunotherapy response in cancer is controversial. 70 , 71 , 72 , 73 , 74 Gao et al. observed that the low-risk group classified by a novel pyroptosis-related signature had higher ESTIMATE immune scores and exhibited better responses to ICIs than the high-risk group in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in the ESTIMATE immune scores between the two groups. 74 In the future, optimal predicting biomarkers should not only concern the composition of the immune infiltrates and the feature of the inflammatory response but also disclose heterogeneity in immunological composition, spatial distribution and function. 75 Finally, GSVA indicated that compared to the low-risk group, the high-risk group had higher enrichment scores in tumour-related signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other molecular biomarkers, Marfa et al used the CART analysis to construct a proteomic signature in a series of 85 patients, which differentiates mild from severe cases (based on predicted OS) according to the four most significant protein peaks [81]. Another emerging predictor is differentially expressed genes (DEGs), or differentially expressed exosomal miRNAs, which has already been used in five studies [22,44,59,62,68]. After selection of candidate genes, LASSO regression, which applies a penalty to candidate predictors and eliminates some variables from the final model, was applied in all studies to construct the final gene panel.…”
Section: Ras Status and Molecular Predictorsmentioning
confidence: 99%
“…After selection of candidate genes, LASSO regression, which applies a penalty to candidate predictors and eliminates some variables from the final model, was applied in all studies to construct the final gene panel. All five studies combined the DEGs with clinical predictors and reported merged scores [22,44,59,62,68].…”
Section: Ras Status and Molecular Predictorsmentioning
confidence: 99%